Harnessing the tillering ability of Zea mays ssp. parviglumis in fodder maize breeding - CHOUDHARY, MUKESH; KUMAR, PARDEEP; KASWAN, SANDEEP; JAT, S L (The Indian Journal of Agricultural Sciences, 2021)
Maize (Zea mays L.) has diversified uses in the form of food, feed and fodder. In India green fodder deficit of 61.1 % has been reported. Under this scenario, maize and its wild relatives with its wide adaptability have enormous potential to serve as nutritious fodder. The annual teosinte, Zea mays ssp. parviglumis, the closest ancestor of modern maize has good tillering and re-growth ability. In an experiment on parviglumis, the effect of 30 kg higher nitrogen than recommended dose showed 12.5% and 20% improvement in tiller re-growth ability (multi-cut) and green fodder yield, respectively. In a pilot trial, fresh cut (first cut) and re-growth (at the second cut) whole/unchaffed fodder samples of parviglumis were fed to the adult goats and grower kids (9 months old) of beetal breed. Re-growth based fodder samples were consumed completely (no leftover) by adult goats as well as grower kids, while fresh (first cut) samples had negligible leftover for adult goats but 32% leftover for grower kids. Goats being selective in feeding habits tend to eat soft and leafy parts and avoid hard and thick (stem) parts of fodder plants hence leftover might be lesser if fed to large ruminants. To exploit these traits, parviglumis was crossed to fodder variety, African tall and 11 promising fodder maize inbred lines. The F1 generation of different wide crosses exhibited a good amount of tillering with many tillers ranging from 1 to 15 indicating partial dominant nature of tillering trait and background effect. The further advancement of promising crosses through backcrossing can help to develop multi-tiller as well as multi-cut trait possessing fodder maize cultivars. To the best of our knowledge, this is the first study on the systematic use of Zea mays ssp. parviglumis for harnessing its tillering and re-growth ability in fodder maize breeding programme.